Micronucleated Erythrocytes in Peripheral Blood from Neonate Rats Exposed by Breastfeeding to Cyclophosphamide, Colchicine, or Cytosine-Arabinoside. (28th November 2016) - Gómez-Meda, Belinda C.; Bañales-Martínez, Luis R.; Zamora-Perez, Ana L.; Lemus-Varela, María de Lourdes; Trujillo, Xóchitl; Sánchez-Parada, María G.; Torres-Mendoza, Blanca M.; Armendáriz-Borunda, Juan; Zúñiga-González, Guillermo M.
Abstract : Genotoxic exposure to chemical substances is common, and nursing mothers could transmit harmful substances or their metabolites to their offspring through breast milk. We explored the possibility of determining genotoxic effects in the erythrocytes of breastfeeding rat pups whose mothers received a genotoxic compound while nursing. Ten groups of female rats and five pups per dam were studied. The control group received sterile water, and the experimental groups received one of three different doses of cyclophosphamide, colchicine, or cytosine-arabinoside. Blood smears were prepared from samples taken from each dam and pup every 24 h for six days. There were increased numbers of micronucleated erythrocytes (MNEs) and micronucleated polychromatic erythrocytes (MNPCEs) in the samples from pups in the experimental groups (P < 0.02 ) and increased MNPCE frequencies in the samples from the dams (P < 0.05 ). These results demonstrate the vertical transmission of the genotoxic effect of the compounds tested. In conclusion, assessing MNEs in breastfeeding neonate rats to assess DNA damage may be a useful approach for identifying genotoxic compounds and/or cytotoxic effects. This strategy could help in screening for therapeutic approaches that are genotoxic during the lactation stage and these assessments might also be helpful for developing preventive strategies to counteract harmful effects.